(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the psychological and social characteristics of professors and teachers in the process of modernization of the education system. Also, the issues of professional competence, communicative skills and readiness for innovative activities of teachers in modern educational conditions are scientifically covered. The results of the study show that psychological stability, social adaptability and innovative thinking of teachers are important factors in the process of modernization of education.